Isolation, Colonization, and Chlorpyrifos Degradation Mediation of the Endophytic Bacterium Sphingomonas Strain HJY in Chinese Chives (Allium tuberosum) - Feng, Fayun; Ge, Jing; Li, Yisong; Cheng, Jinjin; Zhong, Jianfeng; Yu, Xiangyang (Journal of agricultural and food chemistry, 2017)
The endophyte–plant interaction can benefit the host in many different ways. An endophytic bacterium strain (HJY) capable of degrading chlorpyrifos (CP) was isolated from Chinese chives (Allium tuberosum Rottl. ex Spreng). The isolated bacterium HJY classified as Sphingomonas sp. strain HJY could use CP as the sole carbon source. After being marked with the gfp gene, the colonization and distribution of strain HJY-gfp were directly observed in different tissues of Chinese chives with a confocal laser scanning microscope. The inoculation of strain HJY-gfp in Chinese chives resulted in a higher degradation of CP inside the plants than in uninoculated plants. With drench application, up to 70 and 66% of CP were removed from shoots and roots of inoculated Chinese chives, respectively. Moreover, up to 75% of CP was removed from the soil containing plants inoculated with HJY-gfp. With foliage application, the applied concentration of chlorpyrifos affected the degradation performance of strain HJY in Chinese chives. Significant differences were observed only between inoculated and uninoculated Chinese chives with the low applied concentration of CP. Together, other than natural endophyte-assisted plant protection for food safety, the interaction of HJY and plant may be also a promising strategy for in situ bioremediation of soil contaminated with CP.